DEVELOPMENT OF A STANDARDIZED APPROACH FOR THE ASSESSMENT OF BOWEL AND BLADDER DYSFUNCTION IN COMMUNITY PAEDIATRICS. (18th May 2018) - Wang, Rebecca; Kanani, Ronik; Mistry, Niraj; Bardisi, Yara El; Santos, Joana Dos
Abstract: BACKGROUND: Bowel and bladder dysfunction (BBD) is a common yet underdiagnosed paediatric condition that describes a constellation of lower urinary tract symptoms (LUTS) associated with constipation and/or encopresis. Many children with BBD have co-morbid neuropsychiatric symptoms (e.g., inattention, anxiety) and psychosocial stressors. Thus, clinical assessment of behavioural symptoms and social risk factors in this population is essential. However, there is no standardized approach for a comprehensive assessment of BBD. OBJECTIVES: We aim to develop and evaluate physician and parent perceptions with 1) a standardized BBD history and physical intake form for physicians, and 2) a parent-reported intake form. DESIGN/METHODS: From June to Oct 2017, a quality improvement study was conducted in the BBD network, an existing paediatric collaborative initiative consisting of 7 community sites with support of the paediatric urology division in a tertiary hospital. Based on literature review and expert opinions, a standardized intake form was developed for BBD assessment with targeted questions for LUTS, constipation, behavioural, dietary, and psychosocial history, along with a physical exam checklist for neurological red flags. Further, a shorter parent-reported intake questionnaire was developed to clarify patterns of dysfunctional voiding symptoms, dietary recall and stool history. Both forms underwent usability testing and iterative refinement. Prior to clinic, families of children referred for BBD were mailed an intake package for completion. During the clinic, physicians were asked to use the standardized intake form for new referrals. Afterwards, both physicians and parents were given anonymous surveys to evaluate their perceptions of the intake process. RESULTS: A total of 8 physicians and 20 parents responded, with 60% of patients being between ages 4–10 and 55% male. Physicians found the standardized intake form to be a useful guide that reminded them to ask about specific urinary symptoms (88% of the time), constipation (75%), and psychosocial history (76%). The majority of physicians (75%) agreed they would use the intake form again and recommended its implementation. Further, parents responded positively by agreeing that the intake package was easy to complete (65%), felt included in care decisions (95%), and had questions answered appropriately (100%). CONCLUSION: In assessment of BBD, a standardized intake form can help guide physicians to efficiently gather a comprehensive history, rule out red flags, and screen for psychosocial risk factors. With refinements, it can potentially help create a common clinical experience and empower more community paediatricians to manage BBD in the future.